PUBLIC ADMINISTRATION DURING THE COVID-19 PANDEMIC AND REFORM DIRECTIONS - Anđelković, Jovana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
During the COVID-19 pandemic, caused by the SARS-CoV-2 virus, every form of company organization and operation has undergone certain changes. The global crisis has highlighted the role of the state and the public sector in emergency situations and tested their readiness to respond to the challenges posed by the pandemic by instituting adaptable and pragmatic solutions while respecting rule of the law. During the pandemic, state and local officials have faced huge challenges, being obliged to deal with rapidly and constantly changing circumstances, they often had to resort to improvisations. In such an extremely, difficult context, it was of great importance to avoid administrative barriers, which could result in the loss of valuable time during the crisis. The pandemic has revealed many weaknesses in the functioning of state and local governments across Europe, including organization issues, change of the workplace (from an office to a home environment), a new mode of interaction with citizens, etc. In developing countries, inadequate legislative provisions, technical solutions and insufficient digitalization have contributed to slowing down the administrative procedures. The aim of this paper is to point out the problems faced by state administrations and local governments during the COVID-19 pandemic, to highlight the examples of good practices and to indicate the directions of reform after the pandemic.
Keywords: civil servants; human resources; organization; transparency; decentralization